Efficacy of Transarterial Chemoembolization (TACE) for Early-Stage Hepatocellular Carcinoma - Muhammad Ramzan, Muhammad Usman Younas, Asim Ali, Khoala Riaz, Abdullah Saeed (Pakistan Journal of Medical & Health Sciences, 2023)
Background and Objectives: The treatments of choice for patients with early-stage hepatocellular carcinoma (HCC) are surgical resection, local ablation therapy, and liver transplantation; however, transarterial chemoembolization (TACE) is commonly performed due to variations among patients and liver diseases. This study aimed to assess the efficacy of TACE in patients with early-stage HCC. Materials and Methods: A retrospective analysis was carried out of all TACE procedures performed PKLI & RC period (July 2019 to June 2023).The study included a total of 97 eligible patients with early-stage HCC ≤5 cm initially treated with TACE. The mean participant age was 63.47±11.02 years; 69 were men (71.1%). The number of Child–Pugh class A patients was the highest (74 patients [76.3%]), followed by Child–Pugh class B (19 patients [19.6%]) and Child–Pugh class C (4patients [4.12%]). Results: A complete response was achieved in 84(86.6%) patients after the first TACE procedure, w ith1-, 2-, and 3-year survival rates of 91.8%, 87.3%, and 75.4%, respectively. In the multivariate analysis, the patients with a low initial alpha-fetoprotein (AFP) ≤ 20ng/mL (p=0.02) and a complete response after the first TACE (p=0.03) were associated with favorable over all survival. Conclusions: TACE can be used to treat patients with early-stage HCC who are unsuitable for ablation or surgery. If patients are well selected, TACE may be an alternative treatment for patients with low AFP levels who respond well to the initial TACE procedure. Keywords: treatment outcome; transarterial chemoembolization; hepatocellular carcinoma; early stage